Critical Role Played by Cyclin D3 in the MyoD-Mediated Arrest of Cell Cycle during Myoblast Differentiation - Cenciarelli, Carlo (American Society for Microbiology, 1999)
During the terminal differentiation of skeletal myoblasts, the activities of myogenic factors regulate not only tissue-specific gene expressions but also the exit from the cell cycle. The induction of cell cycle inhibitors such as p21 and pRb has been shown to play a prominent role in the growth arrest of differentiating myoblasts. Here we report that, at the onset of differentiation, activation by MyoD of the Rb, p21, and cyclin D3 genes occurs in the absence of new protein synthesis and with the requirement of the p300 transcriptional coactivator. In differentiated myocytes, cyclin D3 also becomes stabilized and is found nearly totally complexed with unphosphorylated pRb. The detection of complexes containing cyclin D3, cdk4, p21, and PCNA suggests that cdk4, along with PCNA, may get sequestered into high-order structures held together by pRb and cyclin D3. Cyclin D3 up-regulation and stabilization is inhibited by adenovirus E1A, and this correlates with the ability of E1A to promote pRb phosphorylation; conversely, the overexpression of cyclin D3 in differentiated myotubes counteracts the E1A-mediated reactivation of DNA synthesis. These results indicate that cyclin D3 critically contributes to the irreversible exit of differentiating myoblasts from the cell cycle.